Concentración de Plaquetas en Pacientes Sanos a Diferentes Velocidades de Centrifugación en la Ciudad de Bogotá, Colombia (2023)
Platelets are cells derived from the hematopoietic lineage and from its formation. through the megakaryocyte originating in the bone marrow and according to recent studies in the lung. This process allows platelets to perform functions such as: clots formation, secretion of platelet granules, and formation of eicosanoids and prostaglandins (Holinstat M., 2017 & Roman L.,2021).